SISTEM INFORMASI PERBANKAN SYARI’AH - AAN ANSORI (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten, 2018)
Abstract This research aims to find out about the shari'ah banking information system that could penetrate in various aspects of life, especially economy and services, both from the micro and macroeconomic sectors, which currently play an important role in the interconnection of banking with industry, trade and others. Almost all of them use information technology in making sales and purchase transactions by involving banking services, as intermediaries in conducting transactions. The established shari'ah banking information system will certainly increase the level of transactions and the outflow of digital money input by simply debiting or crediting transactions carried out by customers or service users, with this information system, of course, the banking performance should be up-to-date in information needs of outside parties and adding bank service features to attract as many customers as possible to make transactions easier. Service and the benefits of banking information systems are necessary in the current era when the interbank competition is increasingly stringent in the use of information systems to attract customers to use the information technology. In carrying out its activities, sharia banking cooperates with the information technology sector to develope an Islamic banking information system by creating a special application (app) that can facilitate all existing transaction processes. The reliability of the banking information system is the main factor in conducting banking business, especially sharia banking, which is currently the trend is increasing, so a reliable Sharia Banking Information System is needed